The research of the effects on antioxidant enzymes of yeasts exposed to chromium III chloride salt by adding vitamin C - Çöteli, Ebru; Karataş, Fikret (Gumushane University, 2021)
Recently, yeast are used frequently in biochemical, biotechnological and toxicological studies. In this study, yeast (Saccharomyces cerevisiae) microorganism was exposed to chromium III chloride (CrCl3.6H2O) salt in two different doses (10 and 40 µg/mL) for 12, 24 and 36 hours. 10, 15 and 20 µg/mL of vitamin C was added to the yeast samples exposed to chromium salt. The effect of yeast and chromium interaction on some biochemical parameters in microorganism were investigated. Firstly, the survival rates of yeast samples at 12, 24 and 36 hours were determined. In addition, the amount of antioxidant enzyme activity of Glutathione peroxidase (GSH-Px), Glutathione reductase (GSHRd) and Superoxide dismutase (SOD) and amounts of total protein were measured by spectrophotometer. It was observed that the number microorganism and amounts of protein decreased depending on increasing chromium dose and time in yeast samples, on the other hand, with the introduction of vitamin C, increase the number of microorganism along with amount of protein. Depending on the increasing chromium dose, the activity enzyme GSH-Px, GSH-Rd and SOD of yeast samples were found to be increased. When the control and other groups were compared, it was observed that chromium increased the amounts of antioxidant enzyme activity. However, it has been obtained that different concentrations vitamin C added to the nutrient medium reduces the amounts of enzyme activity. As a result it was concluded that while chromium increases the formation of free radicals in yeast microorganism, vitamin C, reduces the formation of free radicals due to its antioxidant properties. © 2021, Gumushane University. All rights reserved.
Krom III klorür tuzuna maruz kalan mayalara C vitamini katılarak mayaların antioksidan enzimlerine etkisinin araştırılması
Keywords: CrCl3; GSH-Px; GSH-Rd; Saccharomyces cerevisiae; SOD